2015
DOI: 10.1007/s00134-015-4004-x
|View full text |Cite
|
Sign up to set email alerts
|

ICU-acquired candidemia within selective digestive decontamination studies: a meta-analysis

Abstract: The TA constituent of SDD/SOD is associated with a contextual effect on candidemia incidence which is similar in magnitude to that of the conventional candidemia risk factors and against which PAFP partially attenuates. This increase is inapparent within individual SDD/SOD studies examined in isolation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 41 publications
1
27
0
Order By: Relevance
“…Only 45 of the studies are common to this meta-analysis and to the previous meta-analysis of candidemia [121]. This previous meta-analysis [121] was not restricted to the patient population receiving mechanical ventilation and had included a higher proportion of studies with group wide risk factors for candidemia (25 of the 103 studies [121] ) versus only six of the 113 studies included here. As a consequence, there is a lower incidence of candidemia among the studies here versus previously [121].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Only 45 of the studies are common to this meta-analysis and to the previous meta-analysis of candidemia [121]. This previous meta-analysis [121] was not restricted to the patient population receiving mechanical ventilation and had included a higher proportion of studies with group wide risk factors for candidemia (25 of the 103 studies [121] ) versus only six of the 113 studies included here. As a consequence, there is a lower incidence of candidemia among the studies here versus previously [121].…”
Section: Discussionmentioning
confidence: 99%
“…This previous meta-analysis [121] was not restricted to the patient population receiving mechanical ventilation and had included a higher proportion of studies with group wide risk factors for candidemia (25 of the 103 studies [121] ) versus only six of the 113 studies included here. As a consequence, there is a lower incidence of candidemia among the studies here versus previously [121]. However, even within this differently selected set of studies, the incidence of candidemia is again found to be higher among the control groups of SDD studies with a concurrent design than any other type of component group (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In each case, the increased incidence within control groups of CC design studies of topical antibiotics remains apparent in meta-regression models adjusting for other recognized associations. The influence of topical placebo use, concurrent colonization with Candida, and other influences may also have influences in this process [45][46][47].…”
Section: Limitationsmentioning
confidence: 99%